Experimental determination of multiple ionization cross sections in Si by electron impact - Pérez, Pablo Daniel (2015)
The thin sample method is often used to experimentally determine ionization cross sections, especially when focusing on the low overvoltage region. The simplicity of the formalism involved in this method is very appealing, but some experimental complications arise in the preparation of thin films. In this work, a thick sample method was used to measure the Si-K x-ray production cross section by electron impact. The good agreement between the results obtained and the values reported in the literature validates the method and the parameters used. The advantages and disadvantages of the method are discussed and its application is extended to the determination of Si multiple-ionization cross sections, where the very low emission rates (around two orders of magnitude lower than the single-ionization case) make the use of the thin sample method impracticable.